Il romanzo Zamel di Franco Buffoni come un contributo alla letteratura post-gay - Chmiel, Aneta (Romanica Silesiana)
Franco Buffoni’s Zemel as a Contribution to Post-Gay Literature This text, which contains some remarkable references to literature, appears to treat only of homosexuality, gay identity, and its history. In fact, however, an attempt was made to redefine the extensively discussed issue as to go even further and relate it to the roots of humanity: the relationship between sexuality, desire, and identity. Key words: gay identity, gay relationship, desire, homosexuality.